City life - Franklin, Adrian 1955- (SAGE, 2010)
City life grabs you by collar and draws you deep into the sensuous heartland of the western cityscape. Franklin means "life" literally. This is not only an account of the human hopes, desires, obsessions and follies that animate bricks and mortar, but of all the diverse creatures that join in the urban adventure.